2007
DOI: 10.28945/141
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Media Use in Organizations: Identifying Practices Leading to an Alignment Paradox

Abstract: A case study was conducted in a department of a Fortune 500 company to explore multiple media practices. Existing research has been dominated by a focus on the use of single media, and the valuable insights and knowledge gained in this research largely ignore the characteristics and consequences of multiple media use in organizational settings. Three interrelated practices were identified as important for multiple media use patterns: media cycling practices, fluid interdependent media practices, and puzzle zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Although specific ICTs likely have differential effects on electronic meeting multitasking, we argue that focusing on specific ICTs has less relevance in contemporary organizations because many ICTs have multiple capabilities and features embedded in a single device. Although much early work in this area focused on selecting specific ICTs and matching them to tasks (e.g., Daft & Lengel, 1984, 1986Daft, Lengel, & Trevino, 1987), more recent work has pointed to the importance of examining combinatorial ICT use (Chudoba et al, 2005;Munkejord, 2007;Osterlund, 2007;Reinsch et al, 2008;Rice, Hiltz, & Spencer, 2004;Stephens, 2007;Stephens, Sørnes, Rice, Browning, & Saetre, 2008;Turner & Reinsch, 2007;Watson-Manheim & Belanger, 2007), as well as how people use ICTs sequentially and simultaneously. In this study, we adopt the contemporary perspective, and instead of focusing on a single ICT, we consider the simultaneous use of a variety of ICTs as people multitask during FtF meetings.…”
Section: Research Hypotheses and Questionmentioning
confidence: 99%
“…Although specific ICTs likely have differential effects on electronic meeting multitasking, we argue that focusing on specific ICTs has less relevance in contemporary organizations because many ICTs have multiple capabilities and features embedded in a single device. Although much early work in this area focused on selecting specific ICTs and matching them to tasks (e.g., Daft & Lengel, 1984, 1986Daft, Lengel, & Trevino, 1987), more recent work has pointed to the importance of examining combinatorial ICT use (Chudoba et al, 2005;Munkejord, 2007;Osterlund, 2007;Reinsch et al, 2008;Rice, Hiltz, & Spencer, 2004;Stephens, 2007;Stephens, Sørnes, Rice, Browning, & Saetre, 2008;Turner & Reinsch, 2007;Watson-Manheim & Belanger, 2007), as well as how people use ICTs sequentially and simultaneously. In this study, we adopt the contemporary perspective, and instead of focusing on a single ICT, we consider the simultaneous use of a variety of ICTs as people multitask during FtF meetings.…”
Section: Research Hypotheses and Questionmentioning
confidence: 99%
“…Traditional media use studies have assumed that people use ICTs discretely-one at a time and independent of any prior media use. However, recent research-and general observation-has indicated that people can and do use ICTs in combination, whether simultaneously or sequentially (Chudoba et al, 2005;Munkejord, 2007;Osterlund, 2007;Stephens, 2007;Watson-Manheim & Belanger, 2007). Sequential ICT use occurs when people communicate about an activity or project, with one or more other people, through a series of ICTs.…”
Section: Literature Review Different Types Of Ict Usementioning
confidence: 99%
“…Recent research has begun to develop theoretical and qualitatively descriptive accounts of how people use ICTs in combination (Chudoba, Watson-Manheim, Lee, & Crowston, 2005;Munkejord, 2007;Osterlund, 2007;Stephens, 2007;Turner & Reinsch, 2007;Watson-Manheim & Belanger, 2007). Although empirical research has begun to establish the prevalence of this phenomenon, it has tended to rely on data from only one or two organizations.…”
mentioning
confidence: 99%
“…Meanwhile the history of research studies dealing with parallel activities in a work environment spans several decades, communicational and media multitasking can be considered a hitherto unexplored area. Earlier studies chiefly examined various ICT devices in corporate communication separately, in relation to functions (Daft et al, 1987; Daft and Lengel, 1984, 1986); more recent works point out the significance of combined ICT use, together with the role of both sequential and simultaneous tenure (Chudoba et al, 2005; Munkejord, 2007; Osterlund, 2007; Reinsch et al, 2008; Stephens, 2012; Stephens et al, 2008; Turner and Reinsch, 2007; Watson-Manheim et al, 2007).…”
Section: The Typology Of Multitasking Activitymentioning
confidence: 99%